Behavior analysis of dual-star permanent magnet synchronous generator with inter-turn short fault - Amirouche, Elyazid; Iffouzar, Koussaila; Houari, Azeddine; Ghedamsi, Kaci; Aouzellag, Djamal (International journal of modelling & simulation, 2025)
The dual-star PMSMs (DSPMSM) are widely used in high-power applications due to their robustness and reliability. As they mostly work in harsh environments, they are commonly subject to many faults. One of the most dangerous faults is the inter-turn short fault (ITSF), which induces torque vibrations and overheating inside the machine, and may lead to other faults. To properly handle this issue, it must be correctly understood, and the relationship between different machine's quantities (speed, dq currents, fault ratio and resistance) and the severity of the fault (torque's oscillations and short-circuit current) must be established. In this context, this paper presents a detailed analysis of the DSPMSM behavior under a single ITSF, considering the influence of the mentioned quantities and the PWM converter on torque oscillations and short-circuit current. A mathematical model of the machine is developed, and a hysteresis current controller is used to impose the desired direct and quadrature axis stator currents. Simulation tests are conducted by considering different scenarios. Simulation results showed that to reduce fault severity, a trade-off between speed reduction and flux weakening must be accomplished, consequently accepting some performance degradation. Also, results showed the complex behavior of the short-circuit current, as it does not rely linearly on fault parameters.